Transplantation of autologous mesenchymal stromal cells in complete cervical spinal cord injury: a pilot study - Macêdo, Carolina Thé; de Freitas Souza, Bruno Solano; Villarreal, Cristiane Flora; Silva, Daniela Nascimento; da Silva, Kátia Nunes; de Souza, Clarissa Lima e Moura; da Silva Paixão, Daniela; da Rocha Bezerra, Milena; da Silva Moura Costa, Antônio Olímpio; Brazão, Eduardo Santos; Marins Filho, Josildo Pereira; Matos, André Costa; et al. (Frontiers in Medicine, 2024)
Objective: Spinal cord injury (SCI) is a serious condition that can lead to partial or complete paraplegia or tetraplegia. Currently, there are few therapeutic options for these conditions, which are mainly directed toward the acute phase, such as surgical intervention and high-dose steroid administration. Mesenchymal stromal cells (MSC) have been shown to improve neurological function following spinal cord injury. The aim of the study was to evaluate the safety, feasibility, and potential efficacy of MSC transplantation in patients with cervical traumatic SCI.We included seven subjects with chronic traumatic SCI (> 1 year) at the cervical level, classified as American Spinal Cord Injury Association impairment scale (AIS) grade A. Subjects received two doses of autologous bone marrow derived MSC, the first by direct injection into the lesion site after hemilaminectomy and the second three months later by intrathecal injection. Neurologic evaluation, spinal magnetic resonance imaging (MRI), urodynamics, and life quality questionnaires were assessed before and after treatment.Results: Cell transplantation was safe without severe or moderate adverse effects, and the procedures were well tolerated. Neurological evaluation revealed discrete improvements in sensitivity below the lesion level, following treatment. Five subjects showed some degree of bilateral sensory improvement for both superficial and deep mechanical stimuli compared to the pretreatment profile. No significant alterations in bladder function were observed during this study.Transplantation of autologous MSC in patients with chronic cervical SCI is a safe and feasible procedure. Further studies are required to confirm the efficacy of this therapeutic approach.